Organizing Knowledge in the Field of Creative Arts - Binwal, J. C.; Karisiddappa, C. R. (Journal of Information and Knowledge, 1988)
Analyses the basic concepts which provides the central focus to various fields of knwoledge in creative arts. The structural features of these subjects are delineated. The concepts are identified in relation to their tnanifestation in (BS) PMEST facet matrix.